PERANCANGAN WEBTOON “TRACK RECORD” BAGI REMAJA USIA 13-18 TAHUN SEBAGAI MEDIA TENTANG MENJAUHI KENAKALAN REMAJA DI ERA DIGITAL - Syaharani Dewi, Fanidya; Nirwana, Aditya; Sukmaraga, Ayyub Anshari (Ma Chung Press, Universitas Ma Chung, 2024)
The transitional period between childhood and adulthood, is a phase brimming with potential yet fraught with challenges. Deviant behaviors or juvenile delinquency are often triggered by a strong desire for acceptance and self-exploration. These actions not only harm oneself, such as hindering academic achievement or damaging social relationships, but also have negative impacts on the surrounding environment. The authors aim to provide teenagers with insights into the causes and consequences of juvenile delinquency conflicts in the digital era. This Webtoon design on juvenile delinquency in the digital era leverages the advancements of technology in accessing digital comics, utilizing the LINE Webtoon platform as the primary medium for accessing the designed story. The authors chose comics as the primary medium due to their appeal and suitability for teenagers. The Webtoon, titled